Effect of Cryptocurrency Trading and Monetary Corrupt Practices on Nigerian Economic Performance - Segun Kamoru Fakunmoju; Olawale Banmore; Abiodun Gbadamosi; Olajide Idowu Okunbanjo (Bina Nusantara University, 2022)
Digital financial trading has brought a new dimension of financial technology transactions to the globe. Cryptocurrency trading is one of the new dimensions. However, cryptocurrency trading is plagued with unlawful and monetary corrupt practices, unregulated foreign currency markets, and unknown party participants. Thus, it creates the unpredicted challenge of instigating fear in the investors’ minds and scaring away economic agents, and in turn, it adversely affects economic activities. The research investigated the effects of cryptocurrency on the performance of the Nigerian economy. The specific objective was to examine the effect of cryptocurrency trading and monetary and monetary corrupt practices on Nigerian economic performance. The research used primary data through 98 copies of the questionnaire. Tobit regression method of analysis was applied to analyze the data. The finding reveals that cryptocurrency and monetary and monetary corrupt practices have a negative but significant effect on Nigerian economic performance with marginal effects of -0,172 and -0,734 with P < 0,05 as the significance level. The research concludes that cryptocurrency and monetary corrupt practices affect Nigerian economic performance. The research recommends that the government, through the Central Bank of Nigeria (CBN), should regulate and control cryptocurrency trading by using global digital financing system software. The software will monitor and control cryptocurrency trading in Nigeria to enhance cryptocurrency trading to contribute to and increase Nigerian economic activities.